Metal concentrations in Scopoli’s Shearwater (Calonectris diomedea) seabird in Strofades island complex, Greece; Strofades island - Voulgaris, Marios-Dimitrios (2017)
Seabirds are very useful and trustful indicators of environmental pollution and allow researchers to study the dynamics of contaminants in marine ecosystems. More specifically, marine birds can be suitable bioindicators to assess the environmental conditions which characterize areas of interest. Their ecological features correspond immediately and intensely to environmental changes and food supplies, two parameters that are fundamental to assign them as bioindicators. Seabird species can be used also as indicators of fishery supplies since diet composition reflects prey availability and abundance fluctuation of prey appearance, which may also alter seabirds foraging strategy and their distribution pattern. Additionally, potential fluctuations of fish stocks may cause significant population decline to seabirds, specifically to those which constitute generalist or specialist piscivorous species . As a consequence, seabirds is a taxonomically varied group which constitutes the most sensitive indicator between avifauna for monitoring environmental changes caused by natural forces and/or human activities . Information regarding fish stock changes and piscatorial activities such as fisheries overexploitation and supply of discarded unsaleable bycatch can also be obtained by studying seabird behavior, but requires detailed knowledge of marine birds biology and their correspondence to food supply changes. However it is important to highlight that data related to the quantities and the composition of items discarded and potentially used as an additional food source for scavenging seabirds, are very limited in the Eastern Mediterranean Sea. Moreover, seabirds constitute top marine predators, depended exclusively on aquatic environments where they face toxic risk by external contact, by inhalation, and particularly by ingestion of food and water. Thus, long-lived seabirds may act as a bio-indicator for chemical pollution of different origin since they accumulate a wide range of chemical components and other forms of marine pollutants Consequently, these species offer opportunities to detect and assess in a long term basis, toxicological effects of pollutants in marine ecosystems. For example, one of their ecological features that could be affected by chemical pollution, is their population size that varies slightly between years. Juvenile growth rates, hatching success, breeding success, and any behavior change during the incubation period, can be affected by toxic pollutant contamination in the marine foraging areas used during breeding season. Many seabird species accumulate high concentrations of contaminants in their organism. Taking into consideration that are in the highest place of trophic chain, seabirds are suitable “screens” of pollutants that are being amplified via the trophic chain. Also, it has been already proved that they are bioindicators of metal pollutants and used for the determination of origin of mercury in marine trophic levels. Concentrations of metals are often reported for adult birds, but less often for chicks or fledglings. However, juveniles have been proposed as particularly useful indicators for pollution, as they concentrate metals during a specific period of time and from local and definable foraging areas around colony. The target species, namely Scopoli’s Shearwater (Calonectris diomedea) is a pelagic, long lived, migratory seabird, with particularly high degree of site tenacity and mate fidelity. It is characterized as a highly vagrant species according to its pelagic and wide-ranging distribution. More specifically, the breeding sites of this species are located in the Mediterranean basin whereas its wintering grounds are located in the pelagic and coastal equatorial areas of the eastern Atlantic. Its diet mainly includes pelagic and mesopelagic fishes, squids, crustaceans and occasionally zooplankton. These marine organisms can be found in shallow waters and near reefs, and constitute the most common prey caught in shallow waters or near the sea surface. Greece hosts a significant number of Scopoli’s Shearwater colonies on uninhabited islets, spread mainly in central and southern Aegean Sea, southern and northern Ionian Sea and around Crete. Our study area, the Strofades Island complex (37° 15’ N, 21° 00’ E) is a remote group of two small low islets and several rocks, located in the southern Ionian Sea, 32 nm south of Zakynthos Island and 26 nm west of the Peloponnese. The two main islets (Stamfani and Arpyia) host the largest greek colony of the species (about 5,550 breeding pairs), cover an area of 4 km2 and constitute part of the National Marine Park of Zakynthos. Data for metal contamination in seabirds originated from the Strofades Islands are barely exist. One of the aims of this study will be to provide baseline data for metal concentration levels in Scopoli’s Shearwater collected in one of the biggest colonies in Greece for comparative analyses of inter-specific and geographical differences in bioaccumulation.In the present study levels of cadmium (Cd), lead (Pb), copper (Cu), cobalt (Co), nickel (Ni), manganese (Mn) and zinc (Zn) were investigated as potential chemical stressors in the blood of juveniles and adults Scopoli’s Shearwaters in Strofades Island complex colony, in Greece. Blood samples were collected from both juveniles and adult Scopoli’s Shearwaters individuals, during 7 different breeding seasons between 2007 and 2014. The samples were collected in three sub-colonies from the western, southern and eastern part of the Stamfani Island, where fledglings and breeders were captured by hand. An amount of 0.2-0.5 ml per blood sample was collected using a heparinsed syringe and kept in eppendorf vials with ethyl alcohol as preservative. A total number of 238 samples were collected, from which 182 were from juveniles. The process of metal analysis of blood samples involved sample preparation, digestion and metal quantification. The digestion was performed using hot plate and the quantification of metal content was performed by Graphite furnace atomic absorption spectroscopy. The accuracy of the method was verified by analyzing duplicates of the same amount of certified reference material of blood serum. Blanks were also prepared with and acidified Milli-Q water solution with 0.2% HNO3 and treated in the same way to check for any contamination. Statistical differences of metal concentrations were investigated along with relationships with age, gender and nesting site. From toxic metals, cadmium (Cd) ranged between 0.01-0.02 μg/g and lead (Pb) between 0.07-0.53 μg/g, which were close to the respective European standards. Concentrations of essential metals were generally closed to basal levels, compared with other studies. Statistical analysis in juveniles and adults revealed that in relation to body mass there is no significant relationship between the weight of individuals and metals. All metals showed a significant difference with the years. Statistical results indicate significant sexual differences for Cd, Co, Mn, Pb and Zn for both juveniles and adults. Testing for correlation with nesting sites show significant differences for most of the tested metals (Cd, Co, Cr, Mn, Ni, Pb and Zn). Principal Component Analysis (PCA) were used to detect the relationships between metal concentrations (Cd, Co, Cr, Cu, Mn, Ni, Pb, Zn), year, sex and site of for juvenile and adult birds from Strofades Island colony. Results of PCA showed that they represent 34.82% of variance with PC1 representing (18.76%) and PC2 (16.05%). Metal levels tested do not seem to have adverse effects on studied population, but diet analysis of the species will be helpful towards the better understanding of metal uptake.